Neurotransmitter receptor auxiliary subunits - Diaz Alonso, Javier (Henry Stewart Talks, 2023)
Neurotransmitter receptor auxiliary subunits, Transmembrane AMPA receptor regulatory proteins (TARPs), TARPs regulation of AMPA receptor trafficking and function, Other important auxiliary subunits, Other receptors with auxiliary proteins, Auxiliary subunits as therapeutic targets